Income diversification and household welfare in Tanzania 2008-13 - Rumman Khan; Oliver Morrissey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper uses three waves of Tanzanian National Panel Surveys (2008/09, 2010/11, and 2012/13) to construct a panel from 3,676 households that appear in at least two waves to explore the effect of income diversification on household welfare measured in terms of food consumption. The analysis considers four sources of labour income in addition to farming. Increasing diversification is associated with higher welfare, but there are differences by gender and activity type. Non-agricultural wage employment is clearly beneficial, irrespective of gender, and has had relatively high growth. Non-agricultural self-employment is a welfare-increasing diversification strategy, especially in rural areas (although females benefit more than males in urban areas), but growth has been slow. Agricultural wage employment has been a major source of increased employment for females from poorer rural households but appears to be chosen as the only available option as it is not associated with increasing household consumption.
Keywords: I39; O12; O55; 330; income diversification; labour income; gender; household welfare; Tanzania